The Impact of Personal Hygiene and the Use of Personal Protective Equipment on the Incidence of Dermatitis - Yusran Fauzi; Fikitri Marya Sari (Pancasakti Journal Of Public Health Science And Research, 2025)
Skin diseases are commonly caused by bacterial, viral, fungal, parasitic infections, and allergic reactions. According to data from the International Labour Organization (ILO), 160 workers suffer from occupational diseases. Surveillance studies in the United States have reported that 80% of occupational skin diseases are classified as dermatitis. This study aimed to examine the impact of personal hygiene and the use of personal protective equipment (PPE) on the incidence of dermatitis at the Sandar Angin Public Health Center in Pagar Alam City. An analytic survey method with a cross-sectional design was employed. Data were collected using a questionnaire administered to 68 patients who visited the Sandar Angin Public Health Center, selected through accidental sampling. Data analysis was conducted using the Chi-Square test. The results indicated a significant relationship between personal hygiene (p = 0.035) and the use of personal protective equipment (p = 0.010) with the incidence of dermatitis at the Sandar Angin Public Health Center. It is recommended that the health center implement proper personal hygiene practices, particularly after work-related activities, and ensure the consistent use of personal protective equipment to reduce the risk of dermatitis.